The effect and development of dual higher education in disadvantaged areas - Malatyinszki Szilárd; Малатінскі Сілард; Malatyinszki S. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2019)
Abstract. In our research we present the practice of the dual higher education in Hungary and we suggest solution for the difficulties. The spread of dual education can support the rural higher education, as the opportunity to earn income would be very attractive. The extention of immigration would be less as a result of dual cooperation. This way we can help to improve the development of rural companies and firms. We will be able to keep the intellectuals of rural areas and we can give opportunity for the persistency of intellectual capital. The cooperation between the companies and the higher education institutions gives opportunity to reduce recruitment costs, the students to fit in and the educational institutes to approach the practical area of the competitive sector. We suggest to renew the full system into a flexible and real-lifelike system based on the experiences of the past years.

Kutatásunkban bemutatjuk a duális felsőfokú képzést Magyarországon. A duális felsőoktatási együttműködések lehetőséget adnak a cégeknek a toborzási költségeik csökkentésére, a hallgatók beillesztésére, és az oktatási intézmények közelítésére a versenyszféra gyakorlati területei felé, de az elmúlt évek gyakorlati tapasztalatait megismerve javasolt a rendszer felülvizsgálata, a rugalmas és életszerű keretek kialakítása. A duális képzés elterjedése támogathatja a vidéki felsőoktatást, hiszen a hallgatók jövedelemszerzési lehetősége vonzerő lehet. Emellett, ha a vidéki partnercégekkel sikeres együttműködések alakulhatnak ki, akkor a jelentősebb gazdasági potenciált jelentő térségekbe kisebb lehet a kivándorlás mértéke. Így megőrizhetjük a vidék értelmiségét, és helyben adhatunk lehetőséget a szellemi tőke megmaradására.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2019_tom-vi_vi-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008405
Keywords: practice of the dual higher education; competitive sector